2003
DOI: 10.1021/jp030554z
|View full text |Cite
|
Sign up to set email alerts
|

Infrared, Density-Functional Theory, and Atoms in Molecules Method Studies on Conformers of Some 2-Substituted 1H-Pyrroles

Abstract: Methyl pyrrole-2-carboxylate (MPC), pyrrole-2-carbaldehyde (PC), methyl N-methylpyrrole-2-carboxylate (MPC-NMe), and N-methylpyrrole-2-carbaldehyde (PC-NMe) are investigated. Experimental and theoretical IR spectra and density-functional theory calculations concerning energetic and geometrical properties of molecular structures show that for all species s-cis conformers are more stable than s-trans ones. The existence of intramolecular N−H···O hydrogen bonds for s-cis conformers of MPC and PC is controversial;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
27
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 40 publications
11
27
1
Order By: Relevance
“…[1] The intermolecular HB interaction between two molecules of pyrrole-2-carbaldehyde derivatives has been studied by means of spectroscopic, diffraction, and theoretical methods including the Bader theory of atoms in molecules. [2][3][4][5] The calculated HB energy for these dimers is comparable with the HB energy found for many typical acid dimers. [6] Its value is À6.90, À6.23, À6.45, À6.63, À5.26, and À5.90 kcal/mol for a single N-H⋯O interaction within the pyrrol-2-carbaldehyde dimer, [7] pyrrol-2-yl methyl ketone dimer, pyrrol-2-yl dichloromethyl ketone dimer, pyrrol-2-yl trichloromethyl ketone, [5] and pyrrole-2-carboxylic acid dimers, [3] respectively.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…[1] The intermolecular HB interaction between two molecules of pyrrole-2-carbaldehyde derivatives has been studied by means of spectroscopic, diffraction, and theoretical methods including the Bader theory of atoms in molecules. [2][3][4][5] The calculated HB energy for these dimers is comparable with the HB energy found for many typical acid dimers. [6] Its value is À6.90, À6.23, À6.45, À6.63, À5.26, and À5.90 kcal/mol for a single N-H⋯O interaction within the pyrrol-2-carbaldehyde dimer, [7] pyrrol-2-yl methyl ketone dimer, pyrrol-2-yl dichloromethyl ketone dimer, pyrrol-2-yl trichloromethyl ketone, [5] and pyrrole-2-carboxylic acid dimers, [3] respectively.…”
Section: Introductionsupporting
confidence: 65%
“…Electron density at the H⋯Y BCP is also an indicator of HB strength because correlations between this value and the other descriptors of an HB interaction have been found. [26] To acquire better insight into a nature of the intramolecular interactions within 2-acylpyrrole molecules (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), their electronic structure were also characterized by natural bond orbital (NBO)-based charge transfer descriptors such as perturbative energy lowering ΔE n → σ* . [27] The main goal of this work was to discuss whether QTAIM topological parameters in connection with NBO analysis could be an effective tool for the recognition of an intramolecular interaction within a set of 2-acylpyrroles 1-20 (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of both N,O-cis and N,O-trans conformations has been detected by FTIR for a series of 2-pyrrolyl chloromethyl ketones and 1-methyl-2-pyrrolyl chloromethyl ketones in cyclohexane solution [38]. In this case, the conformational stability is, however, governed Populations of individual conformers (P in %) are also tabulated [39][40][41][42][43][44][45], indicate that their N,O-cis conformers possess lower total electron energies than the respective N,O-trans conformers, which fully corresponds with the energetic ordering of the cc-and tt-conformers for 4a and 5a.…”
Section: Relative Energiesmentioning
confidence: 99%
“…Previous experiments in the gas phase, by microwave spectroscopy 4 and infrared in supersonic jet expansion, 3 and in solutions [5][6][7] as well as theoretical investigations 3,5,8 showed that P2C adopts the conformation where the N-C-CdO dihedral angle is in the cis orientation ( Figure 1). The trans conformer has a high relative energy, and its equilibrium population at room temperature was estimated to be very low, ,1%.…”
Section: Introductionmentioning
confidence: 95%